Release agent and lubricant composition, method for molding coating film, and dry coating film

By using a high melting point silicone resin and a liquid 1,2-polybutadiene release agent and lubricant composition in molding processing such as fiber reinforced plastics, the problems of insufficient heat resistance and damaged coating are solved, and a dry coating with high density and heat resistance are achieved, which is suitable for repeated molding.

CN119907739APending Publication Date: 2025-04-29YUSHIRO CHEM IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380067839.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-21
Filing Date
2023-03-17
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The prior art has problems in molding processing such as fiber reinforced plastic (FRP) and other problems such as heat resistance, high-speed molding leads to damage to the coating, and consolidation of the processed materials into tools and molds.

Method used

A release agent-lubricant composition is used to form a mesh structure by radical polymerization reaction of high melting point silicone resin and liquid 1,2-polybutadiene, and is coated on a mold and heat-cured to form a dry coating.

Benefits of technology

The adhesion and heat resistance of the mold release agent coating are improved, ensuring that it is not easy to deteriorate or break during repeated molding, and no toxic gas is generated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005322237750000121
    Figure BDA0005322237750000121
  • Figure BDA0005322237750000131
    Figure BDA0005322237750000131
  • Figure BDA0005322237750000171
    Figure BDA0005322237750000171
Patent Text Reader

Abstract

Provided is a mold release agent / lubricant composition which has excellent lubricity and mold release properties, has high heat resistance, prevents seizure between a material to be processed and a mold, and has good mold release properties between the material to be processed and the mold even when repeatedly molded. The release agent and lubricant composition is characterized by containing a silicone resin having, as a main constituent unit, a T unit represented by RSiO3 / 2 (R represents an organic functional group), liquid 1, 2-polybutadiene, and a solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a mold release agent / lubricant composition suitable for molding of fiber reinforced plastics (FRP) and the like. Background Art

[0002] In the molding process, a mold release agent is used to prevent the processed material from being fixed to the tool or mold. As mold release agents used in the past, there are mold release agents in which silicone oil, perfluoropolyether, and fluororesin (polytetrafluoroethylene) powder are dissolved or dispersed in a solvent alone or in combination, and mold release agents in which surfactants are added to these compounds and emulsified or dispersed in water.

[0003] On the other hand, in the molding of fiber reinforced plastics (FRP) and the like, from the viewpoint of improving heat resistance and mechanical strength, so-called super engineering plastics such as polyphenylene sulfide, polyetheretherketone, aliphatic polyamide and polyamideimide are used as matrix resins, and there is a tendency to increase the temperature during compression molding or injection molding. In addition, in the molding of fiber reinforced plastics (FRP), thermosetting resins were mainly used in the past, but from the perspective of expanding the use to automobiles requiring mass production, thermoplastic resins have begun to be used to promote the high-speed molding (patent document 1). In addition, from the viewpoint of mass production, it is expected that even if molding is repeated, the coating film will not deteriorate or break. From such a background, in the past, the film damage caused by insufficient heat resistance and high-speed molding occurs in the release agent, and the problem of the processed material being solidified to the tool and the mold occurs.

[0004] As a release agent and lubricant with excellent heat resistance and repeated molding processability, there is a release agent composition (patent document 2) comprising styrene-diene block copolymer, functional silicone, solvent and one or both of a catalyst and a cross-linking agent according to the situation. In patent document 2, in order to improve the resistance of forming a film and improve repeated molding processability, the application of functional silicone and the promotion of the cross-linking reaction of a catalyst and a cross-linking agent are carried out. However, the release agent composition of patent document 2 is not sufficient for the improvement of repeated molding processability when used only once, although the heat resistance, lubricity and demoulding properties are improved. In addition, the application of functional silicone and the cross-linking reaction of a catalyst and a cross-linking agent contribute to the curing of the film formed by the release agent composition, but it is not synonymous with the improvement of the adhesion of the release agent film to the tool and the mold required in repeated molding, and there is a limit to repeated molding. In a mold sintering release agent in which amino-modified silicone, blocked polyisocyanate, and polyol are dissolved or dispersed in a liquid, a film having excellent releasability and adhesion can be formed in a short time at a sintering temperature as low as 150° C. or less (Patent Document 3). However, since the film has a urethane bond with low heat resistance, there is a problem with heat resistance during repeated molding.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-70080

[0008] Patent Document 2: Japanese Patent Application No. 2009-519849

[0009] Patent Document 3: Japanese Patent No. 6869480 Summary of the invention

[0010] Problems to be solved by the invention

[0011] An object of the present invention is to provide a mold release agent and lubricant composition which has excellent lubricity and mold release properties, has high heat resistance, prevents seizure between a workpiece and a mold, and has good mold release properties between a workpiece and a mold even after repeated molding.

[0012] Means used to solve problems

[0013] In the present invention, it was found that a lubricant containing a specific silicone resin having a high melting point and becoming a hard resin when solidified and liquid 1,2-polybutadiene forms a network structure through free radical polymerization reactions within and between molecules, thereby improving the adhesion of the release agent coating and functioning as a release agent and lubricant composition, thereby completing the present invention.

[0014] The release agent and lubricant composition of the present invention is characterized in that it contains RSiO 3 / 2 A silicone resin in which the T unit represented by (R represents an organic functional group) is a main structural unit, liquid 1,2-polybutadiene and a solvent.

[0015] The molding method of the present invention is characterized by comprising: step 1, 3 / 2 A release agent and lubricant composition comprising a silicone resin, liquid 1,2-polybutadiene and a solvent, in which a T unit represented by (R represents an organic functional group) is used as a main structural unit, is applied to a mold to form a coating film; and step 2, heating and curing the coating film at 100 to 400° C. for 3 to 60 minutes to form a dry film on the surface of the mold.

[0016] The dry film of the present invention is characterized in that it is composed of RSiO 3 / 2 The mold release agent / lubricant composition is composed of a silicone resin having a T unit represented by (R represents an organic functional group) as a main structural unit, liquid 1,2-polybutadiene and a solvent.

[0017] The above-mentioned mold release agent and lubricant composition preferably further contains a drying oil.

[0018] The content of the drying oil is preferably 20% by weight or less based on the total amount of the drying oil and the liquid 1,2-polybutadiene.

[0019] The above-mentioned mold release agent and lubricant composition preferably further contains a radical polymerization initiator.

[0020] The processed material has an effect on plastic, glass, synthetic fiber, wood, rubber, stone, cement, concrete, ceramics or a composite material of two or more of them.

[0021] The processed material is particularly effective for fiber-reinforced plastics.

[0022] Effects of the Invention

[0023] The mold release agent and lubricant composition of the present invention contains a silicone resin having T units as main structural units and a lubricant in liquid 1,2-polybutadiene, and forms a network structure through free radical polymerization reaction within and between molecules, and has high adhesion. Therefore, the dry film formed in the mold using such a mold release agent and lubricant composition has high heat resistance and strength, and is not easily degraded or damaged even during repeated molding.

[0024] Furthermore, even when the mold release agent / lubricant composition of the present invention is used for molding of a workpiece, no toxic gas is generated.

[0025] According to the present invention, the formed dry film has high heat resistance and strength and is not easily deteriorated even during repeated molding, so various processed materials can be molded, and a release agent and lubricant composition suitable for molding processing using plastic, glass, synthetic fiber, wood, rubber, stone, cement, concrete, ceramics or a composite material of two or more thereof, especially fiber-reinforced plastics as a processed material can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a diagram showing a method for evaluating the coating strength of a release agent and lubricant composition by a reciprocating sliding friction test.

[0027] Figure 2 This is a diagram showing a method of evaluating the heat resistance of a formed film by visually confirming the transfer of a test material to a test plate during repeated molding in a press test. DETAILED DESCRIPTION

[0028] Hereinafter, the mold release agent / lubricant composition of the present invention will be described in detail.

[0029] The mold release agent and lubricant composition of the present invention comprises RSiO3 / 2 A silicone resin in which the T unit represented by (R represents an organic functional group) is a main structural unit, liquid 1,2-polybutadiene and a solvent.

[0030] Silicone resin is a substance with organic functional groups bonded to silicon. The silicon as the base has four bonding points. The skeleton structure of silicone is divided into M units (monofunctional; RR'R"SiO 1 / 2 ), D unit (2 functional; RR'SiO 2 / 2 ), T unit (trifunctional; RSiO 3 / 2 ) and Q unit (4-functional; SiO 4 / 2 ) These four basic units. R is an organic functional group, and R' and R" are organic functional groups containing hydrogen atoms.

[0031] The silicone resin has a structure combining the above four basic units. Its molecular structure is linear, cyclic, branched or three-dimensional network, and the T unit forms a three-dimensional network structure formed by branching or entanglement. It should be noted that the silicone resin containing the Q unit has a branched structure, and the silicone resin composed of the M unit and the D unit is linear.

[0032] In the present invention, a silicone resin having a T unit having one organic functional group on silicon as a main structural unit (hereinafter also referred to as a "T-type silicone resin") is used.

[0033] In the T-type silicone resin, R is an unsubstituted or substituted hydrocarbon group having 1 to 10 carbon atoms. The hydrocarbon group includes a chain hydrocarbon group and a cyclic hydrocarbon group, the chain hydrocarbon group is an alkyl group and an alkenyl group, and the cyclic hydrocarbon group is a phenyl group. Among them, an alkyl group without an unsaturated bond is preferred, specifically a methyl group. It should be noted that a part of the hydrogen atoms of the above hydrocarbon group may be substituted by a nitro group, a sulfo group or an amino group within the range that does not impair the effect of the present invention.

[0034] T-type silicone resins include (CH3)2HSiO 1 / 2 Unit, (CH3)3SiO 1 / 2 Unit and (CH3)SiO 3 / 2 The copolymer formed by the unit, (CH3)2HSiO 1 / 2 Unit and (CH3)SiO 3 / 2 The copolymer formed by the unit, (CH3)2HSiO 1 / 2 Unit, (CH3)SiO 3 / 2 Unit and (C6H5)3SiO 1 / 2 Copolymers formed by units, etc.

[0035] Commercially available products include X-48-1030, X-40-2756, and X-48-5030 (in Table 2, silicone resins A to C are all manufactured by Shin-Etsu Chemical Co., Ltd.).

[0036] Liquid 1,2-polybutadiene is polybutadiene having vinyl double bonds. Liquid 1,2-polybutadiene is preferably composed of only monomer units having vinyl double bonds. Liquid 1,2-polybutadiene has a large number of double bonds in the side chain, so a large amount of free radicals are generated, and silicone resin and 1,2-polybutadiene undergo a polymerization reaction, thereby forming a mesh structure.

[0037] The liquid 1,2-polybutadiene referred to in this specification includes, in addition to 1,2-polybutadiene, 1,2-polybutadiene diol and substances having a hydrogen (—H) or hydroxyl (—OH) group at the terminal.

[0038] The number average molecular weight (Mn) of the liquid 1,2-polybutadiene is usually 500 to 100,000, preferably 500 to 10,000, more preferably 500 to 5,000, and particularly preferably 500 to 3,000.

[0039] Commercially available products include B-1000 (terminal structure H, number average molecular weight (Mn) 1200, viscosity (45°C) 1000 mPa·s), B-3000 (terminal structure H, number average molecular weight (Mn) 3200, viscosity (45°C) 21000 mPa·s), and G-3000 (terminal structure OH, number average molecular weight (Mn) 3000, viscosity (45°C) 31000 mPa·s) (in Table 2, polybutadienes A to C are all manufactured by Nippon Soda Co., Ltd.).

[0040] In the release agent and lubricant composition, the content ratio of the T-type silicone resin and the liquid 1,2-polybutadiene is usually 0.2 to 2 parts by weight, preferably 0.3 to 1 part by weight of the liquid 1,2-polybutadiene per 5 parts by weight of the T-type silicone resin.

[0041] The solvent for dissolving the T-type silicone resin and liquid 1,2-polybutadiene is not limited as long as it is a solvent in which these compounds can be dissolved. For example, commercially available solvents such as propylene glycol monomethyl ether acetate (PGMAC), isohexane, dipropylene glycol dimethyl ether, 2-methylpentane, 3-methylpentane, 2,2-dimethylbutane and 2,3-dimethylbutane, toluene, xylene, ethyl acetate, butyl acetate, methyl ethyl ketone, methyl isobutyl ketone, solvent naphtha, etc. can be used directly. The dilution amount of the solvent is appropriately determined according to the film thickness (thickness of the dry film) and the coating method. It should be noted that the film thickness is usually 1 to 10 μm, preferably 2 to 5 μm.

[0042] In the release agent and lubricant composition, the T-type silicone resin reacts with liquid 1,2-polybutadiene, specifically, undergoes a radical polymerization reaction, thereby forming a strong network structure between and within molecules, thereby improving the adhesion of the release agent film.

[0043] The mold release agent / lubricant composition preferably contains a drying oil in addition to the T-type silicone resin and liquid 1,2-polybutadiene.

[0044] Drying oil has an iodine value (IV) of 130 or more, and forms a film and solidifies by reacting with oxygen in the air. The iodine value is the number of grams of iodine that can be added to 100 grams of oil or fat, and a higher value indicates a higher content of unsaturated fatty acids.

[0045] Examples of drying oils include linseed oil (IV170-204) and tung oil (IV155-175). Drying oils can generate free radicals at a lower temperature than liquid 1,2-polybutadiene. The drying oils promote the generation of free radicals in liquid 1,2-polybutadiene, so a dry film can be formed even at a lower temperature.

[0046] The content of the drying oil is preferably 20% by weight or less, more preferably 5 to 20% by weight, relative to the total amount of the drying oil and the liquid 1,2-polybutadiene. By containing the drying oil in the above amount, the mold release agent and lubricant composition has excellent heat resistance, lubricity and mold release properties, and the dry film is not easily deteriorated or damaged even after repeated molding. If the content of the drying oil is too much relative to the total amount of the drying oil and the liquid 1,2-polybutadiene, the desired film strength may not be obtained.

[0047] The release agent and lubricant composition preferably further contains a radical polymerization initiator. As the radical polymerization initiator, any of a photopolymerization initiator and a thermal polymerization initiator can be used.

[0048] The photopolymerization initiator is a benzophenone compound, an acetophenone compound, an acylphosphine oxide compound, a titanocene compound, an oxime ester compound, a benzoin ether compound, benzyl and thioxanthone, etc. Specific examples include benzophenone, benzyl dimethyl ketal, 2,2-diethoxyacetophenone, 2,2-dimethoxy-1,2-diphenylethane-1-one, 3,3-dimethyl-4-methoxy-benzophenone, isopentyl p-dimethylaminobenzoate, ethyl p-dimethylaminobenzoate, p-methoxybenzophenone, 1-hydroxycyclohexyl phenyl ketone, methyl phenyl glyoxylate, ethyl phenyl glyoxylate, 2-hydroxy-2-methyl-1-phenylpropane-1-one and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, etc.

[0049] Thermal polymerization initiators include azo compounds and organic peroxides.

[0050] Examples of the azo compound include azobisisobutyronitrile, 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(isobutyronitrile), 2,2'-azobis-2-methylbutyronitrile, 1,1'-azobis(1-cyclohexanecarbonitrile), 2,2'-azobis(methyl isobutyrate) and 2,2'-azobis(2-amidinopropane) dihydrochloride.

[0051] Examples of the organic peroxide include dicumyl peroxide, di-tert-butyl peroxide, tert-butyl peroxybenzoate, tert-butyl hydroperoxide, benzoyl peroxide, cumyl hydroperoxide, diisopropylbenzene hydroperoxide, p-menthane hydroperoxide, and di-tert-butyl peroxide.

[0052] The content of the radical polymerization initiator is not particularly limited, but is generally 0.01 to 0.5% by weight, preferably 0.01 to 0.1% by weight, relative to the total weight of the release agent and lubricant composition. Within this range, the curing speed of the release agent and lubricant composition and the strength of the film are both excellent. If the content of the radical polymerization initiator is too small, the effect of reducing the film formation temperature and shortening the reaction time cannot be fully exerted, and even if it is too much, the reaction cannot be promoted, so the cost advantage disappears.

[0053] The mold release agent and lubricant composition of the present invention is applied to the necessary part of the mold, and is heated and cured to form a dry film, and is used for molding plastic, glass, synthetic fiber, wood, rubber, stone, cement, concrete, ceramics, or a composite material of two or more thereof as a workpiece (object material). The mold release agent and lubricant composition is particularly suitable for molding composite materials such as so-called fiber reinforced plastics (FRP) in which fibers such as carbon fibers and glass fibers are added to plastics to increase strength.

[0054] The method for forming the dry film comprises: step 1 of applying the release agent and lubricant composition to a mold to form a coating film; and step 2 of curing the coating film by heating at 100 to 400° C. for 3 to 60 minutes to form a dry film on the surface of the mold.

[0055] A representative example of the molding process of fiber reinforced plastics (FRP) is RTM (Resin Transfer Molding). RTM is a molding method in which a base material of FRP such as carbon fiber or glass fiber is placed in a mold, and then a resin is injected and cured. It consists of a shaping step 1 and a molding step 2. In step 1, a fabric such as carbon fiber or glass fiber is cut into a specified shape, arranged in an aligned position and direction, and a preform shaped into a product shape is arranged in a mold consisting of a cavity (female mold) and a core (male mold). Next, a release agent and lubricant composition is applied to the surface of the cavity and core of the mold, and the mixture is heated and cured in a drying furnace or an open flame to form a dry film in the mold. In step 2, the resin and the curing agent are mixed and injected into the mold at a relatively high pressure to make the resin flow between the fibers of the preform. The mold is filled with the resin and heated to cure it to obtain a molded product.

[0056] It should be noted that in the molding process of fiber reinforced plastics, in addition to RTM, there are also autoclave molding, press molding, sheet winding molding, filament winding molding, continuous drawing (pultrusion) molding and injection molding, and the release agent and lubricant composition of the present invention can be suitably used in any molding method.

[0057] Example

[0058] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples, but the present invention is not limited to these Examples and the like.

[0059] [Evaluation of release agent and lubricant composition]

[0060] (1) Film strength

[0061] The strength of the film formed from the release agent / lubricant composition as a sample was evaluated by the reciprocating sliding friction test shown in Table 1.

[0062] like Figure 1 As shown in FIG. 1 , the sample is coated on the SPCC-SB steel plate in a thickness of 3 to 4 μm and dried. For samples that require heating treatment, a silicon-aluminum electric furnace is used to heat under specified conditions. After cooling at room temperature, as shown in FIG. Figure 1 As shown in the figure, a steel ball is pressed with a predetermined load and slid at a predetermined speed. The number of sliding times until the film formed by the coating breaks, the friction coefficient increases, and a stick-slip sound occurs is evaluated as the coating strength.

[0063] [Table 1]

[0064] Testing machine Adhesion-slip test machine Breadboard SPCC-SB Test steel ball SUI-J, 3 / 16 inch Load 39.2N Slide speed 4mm / s Slide distance 10mm Evaluation Project Number of slides

[0065] The coating strength was evaluated as A when the number of sliding was 40 or more times, B when the number of sliding was 30 to 39 times, and C when the number of sliding was less than 30 times.

[0066] (2) Heat resistance

[0067] pass Figure 2 In the press test shown above, the presence or absence of transfer of the test material to the test plate during repeated molding was visually confirmed, and the heat resistance of the film formed by the release agent and lubricant composition was evaluated.

[0068] Heat to 300°C by hot pressing. Apply the sample to a SKD-61 test plate in a thickness of 3 to 4 μm and dry. For samples that require heat treatment, use a silicon-aluminum electric furnace to heat under specified conditions. Heat the two test plates to 400°C, place the test material on one test plate, clamp the test material between the two test plates, press it in a thickness of 2 mm to 1 mm, and hold it for 1 minute. The test material uses thermoplastic CFRP (PAN-based carbon fiber + PEEK). Then, release the pressure and let it cool at room temperature. Confirm by visual inspection and finger touch whether the coating is peeled off from the test material. Repeat the test until peeling is observed to evaluate the heat resistance.

[0069] Regarding the evaluation of heat resistance, A was defined as 8 times of molding, B as 4 to 7 times, and C as 3 times or less.

[0070] (3) Transferability

[0071] When the mold release agent and lubricant composition remains after processing in an actual machine, especially when the silicone resin remains or is transferred to the molded product, it becomes a major cause of poor coating and poor adhesion of the molded product in the next process. Therefore, the peak intensity (cps / mA) of silicon remaining on the surface of the test material after the heat resistance evaluation test was measured using a fluorescent X-ray analysis microscope (XGT-7200, manufactured by Horiba, Ltd.) to evaluate the transferability.

[0072] Regarding the transferability, a silicon strength [cps / mA] of less than 50 was designated as A, a silicon strength of 50 or more and less than 150 was designated as B, and a silicon strength of 150 or more was designated as C.

[0073] In addition, the transferability was not evaluated for the comparative examples not containing silicon.

[0074] [Preparation of release agent and lubricant composition]

[0075] Examples 1 to 18 and Test Examples 1 to 2 prepared samples according to Tables 2 to 3, and Comparative Examples 1 to 11 prepared samples according to the compounding ratios shown in Tables 4 to 5.

[0076] [Example 1]

[0077] 10 parts by weight of X-48-1030 (T-type silicone resin, manufactured by Shin-Etsu Chemical Co., Ltd.), 0.25 parts by weight of B-1000 (liquid 1,2-polybutadiene, manufactured by Nippon Soda Co., Ltd.), and 89.75 parts by weight of propylene glycol monomethyl ether acetate were mixed to prepare a release agent and lubricant composition.

[0078] The mold release agent and lubricant composition was applied to a mold and heated at 200° C. for 20 minutes to form a dry film, and the film strength, heat resistance, and transferability were evaluated.

[0079] Table 2 shows the compounding amount of each component of the mold release agent / lubricant composition and the evaluation results.

[0080] [Examples 2 to 8]

[0081] A T-type silicone resin, liquid 1,2-polybutadiene, a solvent, and other components were mixed in the same manner as in Example 1 in the types and amounts shown in Tables 2 and 3 to prepare a release agent and lubricant composition.

[0082] A dry film of the release agent and lubricant composition was formed under the same conditions as in Example 1, and the film strength, heat resistance, and transferability were evaluated.

[0083] In Example 6, X-48-5030 (T-type silicone resin, manufactured by Shin-Etsu Chemical Co., Ltd.) recommends UV irradiation, so UV irradiation was performed. The mold release agent and lubricant composition was applied to the mold, heated at 200°C for 20 minutes, and UV irradiation was performed using a black light lamp (MidBeam2.0) [accumulated light amount 2824 (mJ / cm 2 )] to form a dry film.

[0084] [Examples 9 to 11]

[0085] X-48-1030 (T-type silicone resin, manufactured by Shin-Etsu Chemical Co., Ltd.), B-1000 (liquid 1,2-polybutadiene, manufactured by Nippon Soda Co., Ltd.), linseed oil and propylene glycol monomethyl ether acetate were mixed in the amounts shown in Tables 2 and 3 to prepare a release agent and lubricant composition.

[0086] The above-mentioned release agent and lubricant composition was applied to the mold, heated at 150°C for 20 minutes in Example 9, heated at 100°C for 60 minutes in Example 10, and heated at 180°C for 20 minutes in Example 11 to form a dry film, and the film strength, heat resistance and transferability were evaluated.

[0087] Table 2 or Table 3 shows the compounding amount of each component of the mold release agent / lubricant composition and the evaluation results.

[0088] [Example 12]

[0089] 10 parts by weight of X-48-1030 (manufactured by Shin-Etsu Chemical Co., Ltd.), 0.7 parts by weight of B-1000 (liquid 1,2-polybutadiene, manufactured by Nippon Soda Co., Ltd.), 0.3 parts by weight of linseed oil, and 89 parts by weight of propylene glycol monomethyl ether acetate were mixed to prepare a release agent and lubricant composition.

[0090] The mold release agent and lubricant composition was applied to a mold and heated at 150° C. for 20 minutes to form a dry film, and the film strength, heat resistance, and transferability were evaluated.

[0091] Table 3 shows the compounding amount of each component of the mold release agent / lubricant composition and the evaluation results.

[0092] [Example 13]

[0093] 10 parts by weight of X-48-1030 (T-type silicone resin, manufactured by Shin-Etsu Chemical Co., Ltd.), 1 part by weight of B-1000 (liquid 1,2-polybutadiene, manufactured by Nippon Soda Co., Ltd.), 0.05 parts by weight of dimethyl 2,2'-azobis(2-methylpropionate) (manufactured by Tokyo Chemical Industry Co., Ltd.), and 88.95 parts by weight of propylene glycol monomethyl ether acetate were mixed to prepare a release agent and lubricant composition.

[0094] The mold release agent and lubricant composition was applied to a mold and heated at 200° C. for 5 minutes to form a dry film, and the film strength, heat resistance, and transferability were evaluated.

[0095] Table 3 shows the compounding amount of each component of the mold release agent / lubricant composition and the evaluation results.

[0096] [Examples 14 to 16]

[0097] A mold release agent / lubricant composition was prepared in the same manner as in Example 13 except that the radical polymerization initiator and propylene glycol monomethyl ether acetate were changed to the types and amounts shown in Table 3.

[0098] The above-mentioned release agent and lubricant composition was applied to the mold, heated at 300°C for 5 minutes in Example 14, heated at 400°C for 3 minutes in Example 15, and heated at 150°C for 10 minutes in Example 16 to form a dry film, and the film strength, heat resistance and transferability were evaluated.

[0099] It should be noted that in Example 16, a black light lamp (MidBeam 2.0) was used while heating, and the cumulative UV irradiation light intensity was 9414 (mJ / cm 2 ).

[0100] Table 3 shows the compounding amount of each component of the mold release agent / lubricant composition and the evaluation results.

[0101] [Example 17]

[0102] 10 parts by weight of X-48-1030 (T-type silicone resin, manufactured by Shin-Etsu Chemical Co., Ltd.), 0.9 parts by weight of B-1000 (liquid 1,2-polybutadiene, manufactured by Nippon Soda Co., Ltd.), 0.1 parts by weight of linseed oil, 0.05 parts by weight of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (manufactured by Tokyo Chemical Industry Co., Ltd.) and 88.95 parts by weight of propylene glycol monomethyl ether acetate were mixed to prepare a release agent and lubricant composition.

[0103] The mold release agent and lubricant composition was applied to the mold, heated at 150°C for 5 minutes, and irradiated with UV light (accumulated light intensity 4707 (mJ / cm 2 )〕 to form a dry film, and evaluate the film strength, heat resistance and transferability.

[0104] Table 3 shows the compounding amount of each component of the mold release agent / lubricant composition and the evaluation results.

[0105] [Example 18]

[0106] In Example 2, a mold release agent and lubricant composition was prepared in the same manner as in Example 2, except that isohexane was used instead of propylene glycol monomethyl ether acetate.

[0107] A dry film of the release agent / lubricant composition was formed under the same conditions as in Example 1, and the film strength, heat resistance, and transferability were evaluated.

[0108] Tables 2 and 3 show the compounding amounts of the components of the mold release agent / lubricant composition and the evaluation results.

[0109] The release agent / lubricant compositions of Examples 1 to 18 all exhibited sufficient performance in terms of film strength, transferability, and heat resistance.

[0110]

[0111]

[0112] [Test for evaluating resistance to repeated molding]

[0113] Using concrete or general-purpose polystyrene (GPPS) as a test material, the release agent / lubricant composition of Example 2 was evaluated for its resistance to repeated molding.

[0114] (Test Example 1)

[0115] The mold release agent / lubricant composition of Example 2 was applied to a template made of S55C (carbon steel), dried, and then heat-treated at 200° C. for 20 minutes.

[0116] Into this form, a mixture of HOME cement sand (Japanese: ホームジャリコン) (Kashima Concrete Transport Co., Ltd.) and water was poured in advance at a thickness of 5 mm and dried at 70° C. for 24 hours. After being left to cool, the concrete was removed from the form, and the transfer state of the release agent and lubricant composition to the concrete was visually confirmed to evaluate the film durability (repeated molding).

[0117] The mold release agent and lubricant composition of Example 2 lasted 8 times of use and had sufficient resistance to repeated molding processes.

[0118] (Test Example 2)

[0119] In the same manner as in Test Example 1, the mold release agent / lubricant composition of Example 2 was applied to a S55C template, dried, and then heat-treated at 200° C. for 20 minutes.

[0120] General-purpose polystyrene (GPPS) (manufactured by PS Japan Co., Ltd.) melted at 200°C was poured into the template with a thickness of 2 mm and left to cool at room temperature for 24 hours. After cooling, the resin molded product was taken out from the template, and the transfer state of the release agent and lubricant composition to the resin molded product was visually confirmed to evaluate the film durability (repeated molding).

[0121] The mold release agent and lubricant composition of Example 2 lasted 8 times of use and had sufficient resistance to repeated molding processes.

[0122] [Comparative Example 1]

[0123] 10 parts by weight of X-48-1030 (manufactured by Shin-Etsu Chemical Co., Ltd.) and 90 parts by weight of propylene glycol monomethyl ether acetate were mixed to prepare a release agent composition.

[0124] The release agent composition was applied to a mold and heated at 200° C. for 20 minutes to form a film, and the film strength, heat resistance, and transferability were evaluated.

[0125] In the release agent composition of Comparative Example 1 to which liquid 1,2-polybutadiene was not added, the film did not form a network structure and sufficient film strength was not maintained.

[0126] [Comparative Examples 2 and 3]

[0127] The silicone resin, polybutadiene and propylene glycol monomethyl ether acetate were mixed in the types or amounts shown in Table 4 to prepare a mold release agent composition.

[0128] A coating film was formed in the same manner as in Comparative Example 1, and the coating film strength, heat resistance, and transferability were evaluated.

[0129] In Comparative Example 2 using an MQ-type silicone resin instead of a T-type silicone resin, no effect was exhibited.

[0130] In Comparative Example 3 in which 1,4-polybutadiene was used instead of liquid 1,2-polybutadiene, the radical polymerization reaction did not proceed and the curing of the coating was insufficient, so the coating strength and heat resistance were rated B.

[0131] [Comparative Example 4]

[0132] A mold release agent composition was prepared by mixing 0.5 parts by weight of B-1000 (liquid 1,2-polybutadiene, manufactured by Nippon Soda Co., Ltd.), 5 parts by weight of TSF4421 (modified silicone oil, manufactured by Momentive Performance Materials Japan), and 94.5 parts by weight of isohexane.

[0133] A coating film was formed in the same manner as in Comparative Example 1, and the coating film strength, heat resistance, and transferability were evaluated.

[0134] In Comparative Example 4 using modified silicone oil instead of silicone resin, the release agent was transferred to the test material due to the oily film, and the heat resistance was poor.

[0135] [Comparative Example 5]

[0136] 5.0 parts by weight of VISPAC 1210 (polyisobutylene, manufactured by Soken Co., Ltd.), paraffin-based mineral oil (kinematic viscosity 46 mm 2 / s, 40°C) 5.0 parts by weight, solvent naphtha 80.0 parts by weight, and X-48-1030 (T-type silicone resin, manufactured by Shin-Etsu Chemical Co., Ltd.) 10 parts by weight were mixed to prepare a release agent composition.

[0137] A coating film was formed in the same manner as in Comparative Example 1, and the coating film strength, heat resistance, and transferability were evaluated.

[0138] In Comparative Example 5 in which polyisobutylene, also a thermoplastic polymer, was used instead of liquid 1,2-polybutadiene, the curing of the molded film was not accelerated, so the heat resistance was poor and the transferability was also poor.

[0139] [Comparative Examples 6 and 7]

[0140] The components shown in Table 5 were mixed to prepare a release agent composition.

[0141] The obtained release agent composition was formed into a film under the conditions shown in Table 5, and the film strength, heat resistance and transferability were evaluated.

[0142] The composition of Patent Document 1 (Japanese Patent Application Laid-Open No. 2014-70080) cannot withstand repeated molding and has poor heat resistance.

[0143] [Comparative Example 8]

[0144] A release agent composition was prepared by mixing 2.45 parts by weight of G-1651EU (styrene-diene block copolymer, manufactured by Kraton Corporation), 1.0 parts by weight of DOWSIL RSN-6018 Resin Intermediate (manufactured by Dow Toray Co., Ltd.), 0.5 parts by weight of SILQUESTA-1122SILANE (silane coupling agent, manufactured by NIKKOR KOGYO CO., LTD.), 0.4 parts by weight of tetrabutyl orthotitanate (manufactured by Tokyo Chemical Industry Co., Ltd.), 81.45 parts by weight of n-butyl acetate and 14.2 parts by weight of solvent naphtha.

[0145] The obtained release agent composition was formed into a film under the conditions shown in Table 5, and the film strength, heat resistance and transferability were evaluated.

[0146] The composition of Patent Document 2 (Japanese National Publication No. 2009-519849) is inferior in transferability and heat resistance.

[0147] [Comparative Examples 9 to 11]

[0148] In Comparative Example 9, DRYFILM RA (PTFE + alternative Freon HFC, manufactured by DuPont, USA) was used, in Comparative Example 10, Chemlease AF-7EZ (fluorine + silicone, Chemturn Japan Co., Ltd.) was used, and in Comparative Example 11, Chemlease HT-S (fluorine + silicone, Chemturn Japan Co., Ltd.) was used to form a coating under the conditions shown in Table 5, and the coating strength, heat resistance and transferability were evaluated.

[0149] The commercially available mold release compositions of Comparative Examples 9 to 11 were not capable of repeated molding. In contrast, the mold release agent and lubricant composition of the present invention had excellent repeated molding properties.

[0150] Tables 4 and 5 show the compounding amount of each component of the release agent composition and the evaluation results.

[0151] [Table 4]

[0152]

[0153] [Table 5]

[0154]

[0155] In Tables 2 to 5, materials used in Examples 1 to 18, Test Examples 1 to 2, and Comparative Examples 1 to 11 are as follows.

[0156] Silicone resin A: X-48-1030 (manufactured by Shin-Etsu Chemical Co., Ltd., active ingredient: about 50%)

[0157] Silicone resin B: X-40-2756 (manufactured by Shin-Etsu Chemical Co., Ltd.), active ingredient: 100%)

[0158] Silicone resin C: X-48-5030 (manufactured by Shin-Etsu Chemical Co., Ltd.), active ingredient: 100%)

[0159] Silicone resin D: WACHER 1038 (manufactured by Asahi Kasei Wacker Silicone Co., Ltd.)

[0160] Silicone resin E: DOWSIL RSN-6018 (Resin Intermediate, manufactured by Dow Toray Co., Ltd.)

[0161] Polybutadiene A: B-1000 (liquid 1,2-polybutadiene, manufactured by Nippon Soda Co., Ltd., concentration: 98% or more, Mw = 1200, viscosity 1000 mPa·s, 45°C)

[0162] Polybutadiene B: B-3000 (liquid 1,2-polybutadiene, manufactured by Nippon Soda Co., Ltd., concentration: 98% or more, Mw = 3200, viscosity 21000 mPa·s, 45° C.)

[0163] Polybutadiene C: G-3000 (liquid 1,2-polybutadiene, manufactured by Nippon Soda Co., Ltd., concentration: 98% or more, Mw = 3000, viscosity 31000 mPa·s, 45°C)

[0164] Polybutadiene D: POLYVEST 130 (1,4-polybutadiene, manufactured by EVONIK JAPAN CO., LTD., viscosity 3000 mPa·s, 20°C)

[0165] Radical polymerization initiator A: 2,2'-azobis(2-methylpropionic acid) dimethyl ester (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0166] Radical polymerization initiator B: di-tert-butyl peroxide (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0167] Radical polymerization initiator C: phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide) (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0168] Silicone oil A: TSF4421 (modified silicone oil, manufactured by Momentive Performance Materials Japan)

[0169] Silicone oil B: XIAMETER SH203 (alkyl-modified silicone oil, manufactured by Dow Toray Co., Ltd.)

[0170] Polyisobutylene: VISPAC 1210 (adhesion enhancer, manufactured by Soken Co., Ltd.)

[0171] Mineral oil A: Paraffin-based mineral oil, equivalent to ISO VG46

[0172] Mineral oil B: paraffin-based mineral oil, equivalent to ISO VG460

[0173] Styrene-diene block copolymer; (G-1651EU, manufactured by Kraton Corporation)

[0174] Silane coupling agent: SILQUEST A-1122SILANE (manufactured by Nichia Corporation)

[0175] Tetrabutyl orthotitanate: manufactured by Tokyo Chemical Industry Co., Ltd.

[0176] DRYFILM RA (PTFE + HFC alternative, made by DuPont, USA)

[0177] Chemlease AF-7EZ (Fluorine + Silicone, Chemturn Japan Co., Ltd.)

[0178] Chemlease HT-S (Fluorine + Silicone, Chemturn Japan Co., Ltd.)

Claims

1. A mold release agent and lubricant composition, characterized in that: Contains RSiO 3 / 2 A silicone resin in which the T unit represented by (R represents an organic functional group) is a main structural unit, liquid 1,2-polybutadiene and a solvent. 2 . The release agent and lubricant composition according to claim 1 , further comprising a drying oil.

3. The release agent and lubricant composition according to claim 2, wherein The content of the drying oil is 20% by weight or less based on the total amount of the drying oil and the liquid 1,2-polybutadiene. 4 . The release agent / lubricant composition according to claim 1 , further comprising a radical polymerization initiator.

5. The release agent and lubricant composition according to claim 1, wherein The processed material is plastic, glass, synthetic fiber, wood, rubber, stone, cement, concrete, ceramic or a composite material of two or more of them.

6. The release agent and lubricant composition according to claim 1, wherein The processed material is fiber reinforced plastic.

7. A film forming method, characterized in that: It has: Step 1: 3 / 2 A mold release agent and lubricant composition comprising a silicone resin having a T unit represented by (R represents an organic functional group) as a main structural unit, liquid 1,2-polybutadiene and a solvent is applied to a mold to form a coating film; and Step 2: Curing the coating film by heating at 100 to 400° C. for 3 to 60 minutes to form a dry film on the surface of the mold.

8. A dry film comprising RSiO 3 / 2 The mold release agent / lubricant composition is composed of a silicone resin having a T unit represented by (R represents an organic functional group) as a main structural unit, liquid 1,2-polybutadiene and a solvent.

Citation Information

Patent Citations

  • A composition that coats substrates to prevent sticking

    JP2009519849A

  • Lubricant composition and molding method using the same

    JP2014070080A